PREVALENCE OF PNEUMOCOCCAL PNEUMONIAE AND OTITIDES IN INFANTS (PROVISIONAL DATA) - S.M. Kharit; S.V. Sidorenko; A.A. Ruleva; A.L. Perova; M.O. Volkova; V.V. Gostev; S.I. Alekseenko; A.V. Orlov ("Paediatrician" Publishers LLC, 2011)
The article contains provisional data from epidemiologic study of pneumococcal opaquecommunity-acquired pneumoniae and acute otitidis mediae among children from 0 to 7 years, admitted to one of St. Petersburg children's hospitals. Etiology definition was carried out via blood and phlegm sampling. Neither bacteriological blood nor sputum analysis proved pneumococcal etiology of the disease in none of 168 admitted patients. However, PCR proved invasive form of pneumococcal pneumonia: pneumococcus was found in 2 (9%) from 22 patients. Streptococcus pneumoniae was found in 23,5% of patients aged 0-3 years and in 21,8% of those aged 4-7 years. Nevertheless PCR has proven pneumococcal etiology in 62,8 and 41.1% of cases respectfully. On the ground of this data following indices were calculated: average prevalence of non-invasive pneumococcal pneumoniae - 58,5:100 000, severe forms of pneumococcal otitidis media that require admittance to hospital - 122,1 for children 0-3 years old, 97,4 per 100 000 - 4-7 years old. Acquired data is much higher than prevalence indices of many controllable infections in the country. Pneumococcal serotyping has shown the following: on 75,9% corresponded to 7-valent and on 95,1% it corresponded to 13-valent conjugated pneumococcal vaccines, registered in the Russian Federation. Thereby antipneumococcal immunization has been proved reasonable against pneumoniae and acute otitides mediae among infants. Inclusion of this vaccination into the national calendar has also been proved reasonable. Key words: pneumococcal pneumonia, otitis, vaccination, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 103-107)